Optimal Configuration of An Annular Sector Duct Filled With Porous Media - Hareem, Hafsa; Iqbal, Mazhar (Communications in Mathematics and Applications, 2018)
In the current study, optimal configuration for finned annulus, filled with porous media, have been investigated to maximize the convective heat transfer and minimize the friction effect subject to constant heat flux boundary conditions. Genetic Algorithm (GA) has been employed to find out the optimal geometry out of vast choices of geometrical parameters; ratio of radii of the inner to outer pipe and sector angle of channel. Finite Difference Method (FDM) is applied to solve the governing mathematical model. Chilton-Colburn’s j factor is employed as the objective function and numerical solutions of the momentum and energy equations are used as function values to the optimizer. The results indicate that for a fixed Prandtl number (Pr) the optimal geometry transforms with the variation in permeability of the porous media which is in line with the physics of the problem.